An Error Analysis of the Use of Prepositions in Students' Descriptive Writing - Riska Nurhamidah (ALTSA Publisher, 2021)
This research aims to identify the types of students’ errors in using prepositional place in the descriptive text made by eighth grade (8) students to identify the cause of errors made by students in using prepositional place. That most of the students did not pay attention to use prepositional correctly in a sentence. This research is qualitative research. The research object shows four types of the error made by students, omission, addition, misordering, and misformation. Based on the data, the frequency of students' error in using prepositional place mainly occurred in prepositional in place in 35 errors. The second is prepositional on with 14 errors. The third is the prepositional place at with 12 errors.